Selling visions for education: What do Australian politicians believe in, who are they trying to convince and how? - Pitman, Tim (Australian Council for Educational Research, 2012)
This article analyses the educational visions put forward by Australian federal politicians in their maiden (first) speeches to Parliament. The theoretical approach was a Habermasian-based analysis of the communication strategies adopted by the politicians, meaning that it was not only the content of the speeches but also the delivery that was the focus of the analysis. The findings reveal bipartisan agreement on the importance of education to personal and national economic prosperity, and the importance of quality in education. There were ideologically opposed beliefs in the importance of personal choice and responsibility in education on the one hand, and the need for a democratic and equitable education system on the other. Communicatively, politicians from both sides preferred axiomatic ‘truths’ as a strategic tool to support their various positions, as opposed to strategies of ‘sincerity’ or ‘rightness’.